Analisis Pendapatan pada Usaha Kerupuk Kulit di Kabupaten Kampar (Studi Kasus UD. Kerupuk Kulit Jon Kenedi) - Vesdia Afifah; Ermi Tety; Yeni Kusumawaty (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
This research analyzed production costs, production, and income obtained from the small-scale animal skin crackers industry Jon Kenedi. This research employed a case study method on local business UD Kerupuk Kulit Jon Kenedi. This industry is the largest, oldest, and most labor-intensive skin cracker business in Kampar Regency. It processes cowhide and buffalo skin into crackers. This research was conducted in December 2022. Data was collected by interviewing and filling out questionnaires directly with the owner of UD Kerupuk kulit Jon Kenedi. The data analysis used in this research was quantitative descriptive analysis using the Microsoft Excel program to analyze production cost, gross income, and profit analysis (net income). The results of the research show that the UD Jon Kenedi Skin Crackers agroindustry incurs production costs of IDR 146,572,050 per month to process 3,205 kg of raw skin so that it can produce 1,726.25 kg of skin crackers with a gross income of IDR 172,625,000 per month and net income of IDR 26,052,950 per month.